Book Reviews (Blackfriars, 1926)
Book Reviews in this Article Mrs. Delany at Court and Among the Wits. King Henry The Fifth's Poet Historical. By W. F. P. Stockley, M.A., T.C.D. The New Testament. The Elements of Ethics. By Charles C. Miltner, C.S.C., Ph.D. The Difficult Commandment. By C. C. Martindale, S.J. Adventures in Catholicism. By Richard Ellison. A Dreamer in Christendom. By Algernon Cecil. The Spirit of St. Therese de l'Enfant Jesus. According to her writings and the testimony of eye witnesses. The Little Brown Company. An anthology of Franciscan Poetry and Prose, gathered by Louis Vincent. With an Introduction by the Very Rev. Father Cuthbert, O.S.F.C., M.A. United Britain. By Susan Cunnington, M.A. Grip-fast History Books, Vol. 5. The Life of Mere Marie Eugenie Milleret de Brou, Foundress of the Assumption Nuns. By Alice Lady Lovat. With a Preface by His Eminence Cardinal Bourne, Archbishop of Westminster. A Pilgrim's Miscellanea. By M. D. Stenson, Author of Shrines of Our Blessed Lady, etc. The Art of Communing with God. By a Christian Brother. National Resurrection. A Plea For Disillusionment. By Eustace Dudley, B.A.Oxon. Preface by Arthur Hungerford Pollen.